Application of Digitalization in Dental Education - A Systematic Review - Spandita Das; Kunal Jha; Ipseeta Menon; Gunjan Kumar; Arpita Singh; Diplina Barman (Indian Journal of Dental Research)
The use of digital technologies in education play a crucial role in providing new and innovative forms of delivering education to teachers and students as well as broadening the learning process. The aim of this systematic review is to summarize existing evidence in order to evaluate the application of digitalization in undergraduate and postgraduate dental education. A literature review was completed using PubMed, SCOPUS and DOAJ search engines, following the search strategy using the PICO criteria, to identify English-language articles published between January 2013 and June 2023 that reported the use of digitalization in dental education. Following thorough research, 1721 articles were identified from e-databases. However, only 14 articles were added to this study after they were screened for eligibility. Quality assessment was performed by a checklist of important parameters using the National Institute of Health (NIH) assessment tool. Two studies focused on the knowledge regarding the utilization of digitalization in dental education, two studies examined the implementation of digitalization in dental education, two studies explored the user experience of utilizing digital dentistry, and eight studies investigated the perception and attitude towards digital dental education. The goal of incorporating digitalization in dental education should be to maximize the effectiveness of the many different digital technologies functioning together in patient care and dental education. The most significant advantage of understanding digital technology is its noteworthy benefits, which include compliance from patients, quick and prompt results and aesthetic outcomes.